2020
DOI: 10.1177/1060028019896894
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Different Triazole Antifungal Agents on the Pharmacokinetics of Cyclophosphamide

Abstract: Background: Cyclophosphamide is one of the most important chemotherapeutic drugs. Known as a widely accepted treatment strategy, chemotherapy may damage the immune function of cancer patients; as a result, invasive fungal infections (IFIs) occur. Triazole antifungal agents are the most acceptable drugs for IFI treatment, especially those infections caused by chemotherapy. Objective: We aimed to investigate the effects of different triazole antifungal drugs, including fluconazole, itraconazole, and ketoconazole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 31 publications
0
13
0
Order By: Relevance
“…Cai et al investigated the influence of different triazole antifungal drugs on the pharmacokinetics of cyclophosphamide, and all tested triazoles, including ITZ, increased the pharmacokinetics of cyclophosphamide in cancer patients, as well as the area under the plasma concentration-time curve of cyclophosphamide ( Cai et al, 2020 ). Importantly, it has been reported that combination with ITZ treatment enhanced the toxicity due to chemotherapy in patients with Hodgkin’s lymphoma, causing severe myelosuppression and neurotoxicity after concurrent administration ( Bashir et al, 2006 ).…”
Section: Discussionmentioning
confidence: 99%
“…Cai et al investigated the influence of different triazole antifungal drugs on the pharmacokinetics of cyclophosphamide, and all tested triazoles, including ITZ, increased the pharmacokinetics of cyclophosphamide in cancer patients, as well as the area under the plasma concentration-time curve of cyclophosphamide ( Cai et al, 2020 ). Importantly, it has been reported that combination with ITZ treatment enhanced the toxicity due to chemotherapy in patients with Hodgkin’s lymphoma, causing severe myelosuppression and neurotoxicity after concurrent administration ( Bashir et al, 2006 ).…”
Section: Discussionmentioning
confidence: 99%
“…The essential parameters, K m and V max values of voriconazole which are listed in Table 1, were obtained from literatures 28–30,32 . The essential parameters, renal clearance, K m , and V max values of fluconazole and itraconazole which are listed in Table 1, were obtained from the SDM system and literature 21,31 . After the models were established, the accuracy of the models were verified by the observed values in published papers 34,35 .…”
Section: Methodsmentioning
confidence: 99%
“…[28][29][30]32 The essential parameters, renal clearance, K m , and V max values of fluconazole and itraconazole which are listed in Table 1, were obtained from the SDM system and literature. 21,31 After the models were established, the accuracy of the models were verified by the observed values in published papers. 34,35 The DDI model was evaluated on the basis of a study in 15 male volunteers (18-55 years of age) receiving 150 mg of crizotinib along with 200 mg of oral ketoconazole.…”
Section: Physiologically Based Pk Model Development and Verification ...mentioning
confidence: 99%
See 1 more Smart Citation
“…Ketoconazole had the greatest effect on the PK of cyclophosphamide among the 3 triazole antifungals. 14 Our previous research results show that posaconazole significantly increased the concentration of selinexor (a selective nuclear export inhibition) in rats, fluconazole, itraconazole, and isavuconazole have significant effects on pharmacokinetics of selinexor and increased plasma exposure of selinexor in rats. 15 , 16 …”
Section: Introductionmentioning
confidence: 94%